The Importance of the Teachers’ Role in Imaginative Play - Håberg, Liv Ingrid Aske; Synnes, Hege Holmqvist (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2024)
This study of Norwegian kindergartens investigates how teachers may support imaginative play, drawing on Vygotsky’s approaches to play and teachers’ positioning in play in terms of different roles. For this study, the empirical investigations were organized as both observations and focus group interviews. The sample was two kindergartens with in total 12 teachers and 44 children aged 3-5 years. The study was conducted in November 2021-April 2022. The analyses point to three main findings; firstly, changes according to daily schedule and content may have effect on play, secondly, the teacher’s role may be an obstacle in play, and thirdly, the teacher’s role may be a driving force in play. In the discussion of these findings, questions are raised about traditions and a lack of competence together can lead to children not receiving sufficient support in imaginative play. However, when the teachers are a play partner who both add new fictional elements and support the fiction by »lending« their experiences, the play’s potential and opportunity space is utilized. The conclusion is that the quality of the teachers’ role and involvement will have an impact on children’s cultural expression in play.